The association between carotenoids and subjects with overweight or obesity: a systematic review and meta-analysis. Issue 11 (12th May 2021) - Yao, Nan; Yan, Shoumeng; Guo, Yinpei; Wang, Han; Li, Xiaotong; Wang, Ling; Hu, Wenyu; Li, Bo; Cui, Weiwei
Abstract : Excess body weight, including overweight and obesity, is one of the major factors influencing human health, and plays an important role in the global burden of disease. Abstract : Background : Excess body weight, including overweight and obesity, is one of the major factors influencing human health, and plays an important role in the global burden of disease. Carotenoids serve as precursors of vitamin A-related retinoids, and are considered to have potential effects on many diseases. However, the influence of carotenoids on people with excess body weight is unclear. Methods : This meta-analysis was conducted to assess the effects of carotenoids on overweight or obese subjects utilizing the available evidence. We searched PubMed, Medline, Cochrane Library, Web of Science and EMBASE databases up to September 2020. Random effects models were used to calculate the standard mean differences (SMDs) and odds ratios (ORs) with their 95% confidence intervals (95% CIs). Results : A total of seven randomized controlled trials and eight observational studies met the inclusion criteria and contained 28 944 subjects and data on multiple carotenoid subgroups, including lycopene, astaxanthin, cryptoxanthin, α-carotene, and β-carotene. In all included Randomized Controlled Trial (RCT), the intervention duration was 20 days at the shortest and 16 weeks at the longest, and the range of intervention doses was 1.2–60 mg d −1 . Our study found that the insufficiency of serum carotenoids was a risk factor for overweight and obesity (OR = 1.73, 95% CI [1.57, 1.91], p < 0.001). Moreover, carotenoid supplementation was significantly associated with body weight reductions (SMD = −2.34 kg, 95% CI [−3.80, −0.87] kg, p < 0.001), body mass index decrease (BMI, SMD = −0.95 kg cm −2, 95% CI [−1.88, −0.01] kg cm −2, p < 0.001) and waist circumference losses (WC, SMD = −1.84 cm, 95% CI [−3.14, −0.54]cm, p < 0.001). Conclusion : In summary, the carotenoids show promising effects in overweight or obese subjects. Additional data from large clinical trials are needed.